2013
DOI: 10.1073/pnas.1314345110
|View full text |Cite
|
Sign up to set email alerts
|

Biologically derived melanin electrodes in aqueous sodium-ion energy storage devices

Abstract: Biodegradable electronics represents an attractive and emerging paradigm in medical devices by harnessing simultaneous advantages afforded by electronically active systems and obviating issues with chronic implants. Integrating practical energy sources that are compatible with the envisioned operation of transient devices is an unmet challenge for biodegradable electronics. Although high-performance energy storage systems offer a feasible solution, toxic materials and electrolytes present regulatory hurdles fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
265
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(275 citation statements)
references
References 87 publications
(106 reference statements)
7
265
0
3
Order By: Relevance
“…The operational energy density of the prototype device, based on the electrical energy generated from the discharge data in Figure 5 normalized by the mass of the stored reactants, is estimated to be 32 Wh kg −1 . This value compares favorably to other recently reported biodegradable batteries, [7,8] albeit further improvements are needed to reach the level of conventional primary batteries such as Li-ion batteries. An important advantage of the present device configuration, in terms of energy density, is that the reactants are stored in the dry, solid state.…”
Section: Battery Operationsupporting
confidence: 62%
See 2 more Smart Citations
“…The operational energy density of the prototype device, based on the electrical energy generated from the discharge data in Figure 5 normalized by the mass of the stored reactants, is estimated to be 32 Wh kg −1 . This value compares favorably to other recently reported biodegradable batteries, [7,8] albeit further improvements are needed to reach the level of conventional primary batteries such as Li-ion batteries. An important advantage of the present device configuration, in terms of energy density, is that the reactants are stored in the dry, solid state.…”
Section: Battery Operationsupporting
confidence: 62%
“…[7,8] The significant rise in power output obtained by increasing the absorbent pad thickness is primarily attributed to the reduced internal cell resistance associated with the increased cross-sectional area for ion conduction in the pad. This can be qualitatively observed by the changes in the linear slope of the polarization curves as the pad thickness is increased.…”
Section: Battery Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…This battery utilized biodegradable polyanhydride as a packaging material. Bettinger and coworkers developed an edible sodium-ion battery 9 with biologically derived melanin electrodes 10 . Potentials up to 0.6 V and currents in the range of 5-20 µA can be generated.…”
Section: Introductionmentioning
confidence: 99%
“…Bettinger et al reported an aqueous sodium-ion battery using the skin pigment melanin as the anode and manganese oxide as the cathode. [7] Such an edible battery breaks down into nontoxic components and generates potentials of 0.6 V for 5 h. [8] Rogers et al developed a fully biodegradable primary battery with a dissolvable magnesium anode and a molybdenum cathode. [9] The battery maintained a stable voltage up to 0.7 V for 24 h in PBS electrolyte.…”
Section: Introductionmentioning
confidence: 99%